Original paperClinical and neuropsychological predictors of the diagnosis of dementia with Lewy bodies - Magierski, Radosław; Sobów, Tomasz; Karlińska, Iwona; Flirski, Marcin; Kłoszewska, Iwona (Archives of Medical Science, 2007)
Introduction: The pattern of clinical symptoms and cognitive impairment in dementia with Lewy bodies (DLB) is different from Alzheimer’s disease (AD). The aim of this study was to determine which clinical or neuropsychological features most accurately predicted the diagnosis of DLB or AD in the early stage of dementia. Material and methods: Sixty-two subjects were included, 20 of those with clinically diagnosed DLB, 23 with AD and 19 cognitively intact controls. An elaborated battery of clinical and neuropsychological tools was applied. Results: There were significant differences in clinical variables between the dementia groups despite similar duration of disease. In comparison to AD patients, the subjects with probable DLB achieved significantly worse scores in the NPI, HIS, UPDRS and ADL scales. The presence/recent history of apathy and visual hallucinations were significantly more frequent in DLB. The onset of neuropsychiatric symptoms was earlier in DLB and the symptoms were more severe in this group. The DLB cases had an increased prevalence of a positive history of REM sleep behaviour disorder and anosmia as well. The DLB group was more impaired in category fluency (animals), visuoperceptual, constructional, and attention tasks. Conclusions: DLB patients have a different profile of clinical symptoms and neuropsychological deficits early in the course of dementia compared to the AD group. Neuropsychological evaluation in AD and DLB reveals multiple cognitive deficits even in early and moderate dementia.